A Three-rooted Mandibular Second Premolar: A Case Report - Zahra Fathi; Saeed Rahimi; Reza Tavakoli; Mahsa Amini (Tabriz University of Medical Sciences, 2014)
Presence of extra roots and canals should be considered before initiation of root canal treatment for the success of endodontic treatment. A mandibular second premolar with three separate roots is very rare and its prevalence has been reported to be around 0.1%. This case report explains non-surgical endodontic treatment of a mandibular second premolar with three separate roots and three separate mesiobuccal, midbuccal, and lingual canal orifices. Close attention to anatomic variations, thorough radiographic examinations, thorough evaluation of the pulp chamber floor, and use of magnifying and optical devices have been recommended for the success of endodontic treatment of mandibular second premolars with complicated root canal system anatomy.